Revisiting factors influencing premature closure of small-scale miners: A case study of quarry mines - Mahlaule, Ntiyiso Ally; Rapholo, Maropene Tebello Dinah; Sengani, Fhatuwani (Journal of Degraded and Mining Lands Management, 2024)
This study accentuates the significant contribution of small-scale mining (SM) to stimulating economic development, providing employment, and developing infrastructure. Nevertheless, the continuing premature shutdown of SM bodes ill for economic recovery. To get an idea of these underlying reasons, a systematic review of all articles published in the scientific literature was calculated using Web of Science, Scopus, and Google Scholar. The application of Boolean operators guided the collection of key insights utilising the PRISMA protocol. Tools like ggplot2 (for graphs) and word clouds in RStudio helped us recognise patterns. Analysis was facilitated with ggplot2, showing boxplots and bar charts of quantitative variables between quarry types and geographical regions. At the same time, word clouds also gave us insights into the most common expressions and, thus, the main reasons behind quarry closures. Further, the research revealed a lack of subsurface geological data, which is needed to estimate mineral resources in SM accurately. It also identified a relation with under-exploration leading to early abandonment which in turn increases the chance of misclassification of mineral reserves. Consequently, the study advocates for further research to devise practical strategies for managing mineral resources effectively in small-scale mining operations.